Histiocytic sarcoma following combination chemotherapy for primary mediastinal germ cell tumor: a diagnostic dilemma - Yaegashi, Hiroshi; Kato, Yuki; Nohara, Takahiro; Izumi, Kouji; Kadono, Yoshifumi; Miyagi, Tohru; Nakashima, Takao; Yoshimura, Kaori; Sato, Yasunori; Harada, Kenichi; Mizokami, Atsushi (International Cancer Conference Journal, 2021)
Histiocytic sarcoma is considered an extremely rare condition. We herein report on a case of histiocytic sarcoma following combination chemotherapy for a primary mediastinal germ cell tumor in a 26-year-old Asian man who visited the General Medicine Department of a hospital with complaints of cough and high fever. Chest computed tomography (CT) imaging revealed a tumor (diameter 10.5 cm) in the anterior mediastinum, with no signs of metastasis, and CT-guided biopsy of the mediastinal tumor revealed the presence of some necrotic cartilages. The patient’s serum α-fetoprotein (AFP) level was determined to be high at 160.4 ng/mL and a primary mediastinal non-seminomatous germ cell tumor was suspected, so the patient was referred to the Department of Urology. Despite the presence of severe thrombocytopenia, the patient was treated using a combination of chemotherapy and intermittent transfusion, which was able to normalize his serum AFP level. However, resection of the mediastinal tumor was unsuccessful due to persistent thrombocytopenia and the patient was subsequently transferred to our hospital for further examination and treatment. Despite management by hematologists, the condition of the patient did not improve; although his AFP level remained normal, the tumor increased in size and then metastasized to the liver and spleen. The general condition of the patient deteriorated and he died 9 months after his first visit. The patient was diagnosed with histiocytic sarcoma following a pathological autopsy. Due to the extremely rare incidence of histiocytic sarcoma, this condition should be a differential diagnosis and the appropriate tests must be conducted to give an exact treatment.